EFFECT OF RELAXATION TECHNIQUES OF LABOR PAIN IN STAGE I INPARTU (Studies in Ponek room Hospital Dr. Sayidiman Magetan) - . SINGGIH D. P.; HIDAYATUN NUFUS; . Suhardono (Jurnal Keperawatan, 2014)
The delivery process can lead to a variety of difficulties and pain during childbirth, pain caused by certain nerve endings that cause his. Problem often encountered in the mother inpartu first stage is pain. The data obtained in the Hospital Dr. Sayidiman Magetan recorded the number of women giving birth for 1 year as many as 420 women giving birth with pain different.. The purpose of this study was to determine the effect of relaxation techniques on labor pain in the first stage inpartu in Ponek room Hospital Dr. Sayidiman Magetan. The design of this study analytic approach pre exsperimental with one group pretest-posttest design, the entire population of mothers inpartu first stage in Ponek room Hospital Dr. Sayidiman Magetan ± 28 mothers, a sample of 17 mothers inpartu first stage is done by consecutive sampling technique. Relaxation techniques dependent variable and the independet variables labor pain. Measuring instrument using the observation sheet. Data processing using editing, coding, scoring, tabulating. The statistical test using the Wilcoxon test. From the results, the labor pain before being given a relaxation technique inpartu almost entirely pain was 15 respondents (88.2%) and after a given relaxation techniques is a mild pain most of the 10 respondents (58.8%). Wilcoxon test results with an error rate of <α = 0.05 level was found that the value ρ = 0.001 <α = 0.05, which means that H1 is accepted. The conclusion of this study a effect of relaxation techniques on labor pain in the first stage inpartu in Hospital Dr. Sayidiman Magetan in 2014.The conclusion of this study on effect of relaxation techniques on labor pain in the first stage inpartu in Hospital Dr. Sayidiman Magetan 2014. The results of this research can be used by midwives to provide relaxation techniques to women who are experiencing pain inpartu first stage of labor in order to reduce labor pain.Keywords: relaxation techniques, pain, inpartu first stage.